2006
DOI: 10.1063/1.2165771
|View full text |Cite
|
Sign up to set email alerts
|

Covariant equilibrium statistical mechanics

Abstract: Abstract:A manifest covariant equilibrium statistical mechanics is constructed starting with a 8N dimensional extended phase space which is reduced to the 6N physical degrees of freedom using the Poincaré-invariant constrained Hamiltonian dynamics describing the micro-dynamics of the system. The reduction of the extended phase space is initiated forcing the particles on energy shell and fixing their individual time coordinates with help of invariant time constraints.The Liouville equation and the equilibrium c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 31 publications
0
57
0
4
Order By: Relevance
“…The relativistic analogue of the Maxwell-Boltzman velocity DF has been proposed by Juttner (1911). However, alternatives to a Juttner DF have been discussed by Horwitz et al (1989) and, recently, by Lehmann (2006) and Dunkel & Hanggi (2007).…”
Section: Discussionmentioning
confidence: 99%
“…The relativistic analogue of the Maxwell-Boltzman velocity DF has been proposed by Juttner (1911). However, alternatives to a Juttner DF have been discussed by Horwitz et al (1989) and, recently, by Lehmann (2006) and Dunkel & Hanggi (2007).…”
Section: Discussionmentioning
confidence: 99%
“…1 [16]. Since then, partially conflicting results and proposals from other authors [17][18][19][20][21] have led to an increasing confusion as to which distribution actually represents the correct generalization of the Maxwellian (1). For example, a recently discussed alternative to Eq.…”
mentioning
confidence: 99%
“…For example, a recently discussed alternative to Eq. (2) is the ''modified'' Jüttner function [18,19] The distribution (3) can be obtained, e.g., by combining a maximum relative entropy principle and Lorentz symmetry [20]. Compared with f J at the same parameter values J MJ & 1=m, the modified PDF f MJ exhibits a significantly lower particle population in the high energy tail because of the additional 1=E prefactor.…”
mentioning
confidence: 99%
“…The dotted (red) and solid (green and pink) lines are the x(y) component of velocity distribution obtained, respectively, by integrating Eqs. (12) and (13) over v y (v x ). We have also used the fact that the temperature parameters in the moving frame are the same as that of the rest frame [14,15].…”
mentioning
confidence: 99%
“…Although Jüttner distribution has been generally accepted and used in high energy and astrophysics [2,3,4,5,6,7,8], some authors suggested several alternatives [9,10,11,12] that can be summarized in terms of the following η-parameterized probability distribution functions (PDFs),…”
mentioning
confidence: 99%